HUBUNGAN PENGETAHUAN IBU TENTANG STIMULASI PERKEMBANGAN DENGAN PERKEMBANGAN MOTORIK KASAR ANAK USIA 3-5 TAHUN DI KELURAHAN SEI SIKAMBING B KECAMATAN MEDAN SUNGGAL - Safitri, Yulia (JURNAL KELUARGA SEHAT SEJAHTERA, 2018)
ABSTRACT                                                                                                          The purpose of this study was to identify the relationship of mother's knowledge about developmental stimulation with gross motor development of children aged 3-5 years in the Village Sei Sikambing B district of Medan Sunggal. The results show there is a close relationship between mother's knowledge about developmental stimulation with gross motor development of children aged 3-5 years in the Village Sei Sikambing B Sunggal Medan District, where P value = 0.00 (P <0.01) from the analysis also shows the correlation (r) of 0.63. It is suggested to mothers in order to dig deeper information from sources that are accurate about the importance and how to stimulate gross motor development of children. Keywords: Knowledge Mother,  Development